Blood Glucose Influence on Cholesterol and Blood Pressure of Patients with Type II Diabetes Mellitus - Idola Perdana Sulistyoning Suharto; Satria Eureka Nurseskasatmata (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The purpose of this study was to determine the blood glucose influence on cholesterol and blood pressure of patients with type 2 diabetes mellitus. This research was correlative analytic study. The sample consisted of 24 respondents. Data analyzed using Spearman’s rho. Spearman's rho test results on blood glucose and cholesterol are a significance value of 0.001 and a correlation coefficient of 0.619. This can be interpreted that there is an influence between blood glucose and cholesterol with a strong relationship. Spearman's rho test results on blood glucose and blood pressure are a significance value of 0.000 and a correlation coefficient of 0.798. This can be interpreted that there is an influence between blood glucose and blood pressure with a strong relationship. The conclusion of this study is that there is an influence between blood glucose with cholesterol and blood pressure in patients with type 2 diabetes mellitus